Enhanced UV protection of ketoconazole using Hyptis suaveolens micro emulsion - Ruttiros Khonkarn (2018)
© 2018 Pakistan Journal of Pharmaceutical Sciences. All rights reserved. Ketoconazole is photolabile antifungal drug. Photochemical reactions may decrease its therapeutic effect or induce toxic compounds. The aim of this study was to prepare ketoconazole loaded microemulsion containing H. Suaveolens oil with antifungal and antioxidant powers in order to obtain effective antifungal formulation. The release study, antifungal activity and photostability test, were then evaluated. The results showed that optimized Hyptis suaveolens microemulsion for ketoconazole loading was selected through construction of pseudo-ternary phase diagrams. It consisted of 12.5% H. Suaveolens oil, 12.5% capryol, 25% tween 80, 25% ethanol and 25% water. Mean globule size was 153 nm, as analyzed by photon correlation spectroscopy. Ketoconazole-loaded Hyptis suaveolens microemulsion and Hyptis suaveolens microemulsion had antifungal activity against Candida albican, Microsporum gypseum and Trichophyton mentagrophyte, showing inhibition zone ranged from 28-37 mm and 23-32 mm, respectively. Ketoconazole was released from Hyptis suaveolens microemulsion more than 90% within 5 days. In the results of photostability test, ketoconazole-loaded Hyptis suaveolens microemulsion gave significantly higher remaining ketoconazole than ketoconazole solution. This study demonstrated that Hyptis suaveolens microemulsion could be used to improve the photoprotection of photolabile drug.